The age-profile of invisible transfers: the true size of asymmetry in inter-age reallocations - Rob́ert Ivań Gaĺ; Endre Szabo\'; Lili Vargha (Hungarian Demographic Research Institute, 2013)
We argue that the institutional composition of funding consumption in the two dependent sections of the lifecycle, childhood and old age, are different. To put it sharply, children are raised by their parents, the elderly rely on society. Since the reallocation of resources within households are not registered in National Accounts, the majority of the resources transferred to children are not visible in contrast to resources flowing to the elderly, which are almost entirely observed in public statistics. For our analysis we apply a recent extension of National Accounts, called the National Transfer Accounts, which include intra-household transfers; and a further, experimental extension, the National Time Transfer Accounts, which quantifies the value of time transferred among household members in the form of unpaid household labor. We show that about one third of the full transfer package flowing to children is registered in the National Accounts and another roughly one third is made visible by the National Transfer Accounts. The remaining one third, which is the value of parents caring for their children, is made visible by the National Time Transfer Accounts. The corresponding shares in funding old age are quite different: nearly 90~percent is observed in public statistics and the two accounting extensions unfold only a~bit more than 10 percent.
Keywords: D1; 300; unpaid household labour; intergenerational transfers; time use survey; National Transfer Accounts; Haushaltsstatistik; Bevölkerungsstruktur; Geschichte; Ungarn